2014
DOI: 10.1111/hsc.12176
|View full text |Cite
|
Sign up to set email alerts
|

A scoping review to understand the effectiveness oflinking schemesfrom healthcare providers to community resources to improve the health and well-being of people with long-term conditions

Abstract: What is known about this topic• People with long-term conditions can experience physical, psychological and social problems making the overall management of their health complex.• Formal health services are unable to sufficiently address patients' psychosocial well-being.• Social prescribing allows referrals to voluntary and community sector services, broadening the scope for supporting patients with psychosocial difficulties. What this paper adds• The roles of health professionals and intervention facilitator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
118
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(123 citation statements)
references
References 24 publications
4
118
0
1
Order By: Relevance
“…Despite the identified concerns, as a result of this intrinsic capacity combined with effective external support many of May et al's (2007) 'interactional', 'relational' and 'skillbased' requirements of change towards 'normalization' were fulfilled. Mossabir et al's (2014) recognition of the specific need for GPs to have a prominent role was fulfilled in this case and this One area where there was a view that such processes could have been enhanced was in relation to impact feedback. In relation to achieving sustainable change, Moran and Avergun's (1997) point to 'tracking and monitoring' as an important motivator for sustaining and embedding change and for some informants, more frequent and detailed response would have been appreciated.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Despite the identified concerns, as a result of this intrinsic capacity combined with effective external support many of May et al's (2007) 'interactional', 'relational' and 'skillbased' requirements of change towards 'normalization' were fulfilled. Mossabir et al's (2014) recognition of the specific need for GPs to have a prominent role was fulfilled in this case and this One area where there was a view that such processes could have been enhanced was in relation to impact feedback. In relation to achieving sustainable change, Moran and Avergun's (1997) point to 'tracking and monitoring' as an important motivator for sustaining and embedding change and for some informants, more frequent and detailed response would have been appreciated.…”
Section: Discussionmentioning
confidence: 75%
“…Despite Mossabir et al's (2014) concerns over the poor evidence base surrounding SP implementation, the literature did provide insights into some relevant variables -both affirmatively (Brandling & House, 2009) and in relation to various 'barriers' (Checkland et al, 2007).…”
Section: The Hcs Projectmentioning
confidence: 99%
See 1 more Smart Citation
“…This support means that they are less likely to feel less socially isolated. A previous scoping review of the literature has demonstrated improvements in health and well-being patients of those with long-term conditions who are linked with appropriate community resources by a facilitator [14].…”
Section: Discussionmentioning
confidence: 99%
“…Such interventions should be tailored, not only to an individual's desires and goals towards socially engagement, but to how social isolation relates to their personal musculoskeletal pain experiences and beliefs. Whilst such strategies may be costly to both health and social care services (Husk et al, 2016;Mossabir et al, 2015), this may be offset through reduced health and service care burden in accident and emergency admissions, formal and informal carer costs and reduced primary and secondary care utilisations (Husk et al, 2016;Landeiro et al, 2016;Lim et al, 2006;Mossabir et al, 2015). Through this, biopsychosocial features of an individual's disease can be sufficiently addressed for sustainable improvements in symptom management and social engagement.…”
Section: Recommendationsmentioning
confidence: 99%